Analysis of Judges' Considerations in Imposing Criminal Sentences for Class 1 Narcotics Abuse for Oneself (Case Study of Labuan Bajo District Court Decision Number 28/Pid.Sus/2023/Pn Lbj) - Fillemon Hendrik Pagula Mamuyab; Gelar Ali Ahmad (Universitas Negeri Surabaya, 2025)
Main objective of this research is to understand the basis of judges' considerations in deciding cases, including the application of Law Number 35 of 2009 on Narcotics, as well as the aspects considered from both juridical and psychological perspectives. The research findings indicate that judges overlooked the facts revealed during the trial when deciding cases of self-use of Class 1 narcotics, failing to consider the provisions in Supreme Court Circular Letter Number 1 of 2017, particularly in the criminal chamber formulation letter (b). This research emphasizes the importance for judges to explore other legal sources, such as the Supreme Court Circular Letter Number 1 of 2017, previous rulings, and expert doctrines, in delivering verdicts against perpetrators of self-use narcotics offenses. If the judge does not consider these legal sources, the resulting verdict may lead to defects in the imposition of punishment. The conclusion of this study is that the judge's considerations in sentencing Defendant I Sarjan alias Jek and Defendant II Abdul Jalani alias Buce did not comply with the provisions of the Supreme Court Circular Letter Number 1 of 2017. Based on research and discussion, the author concludes that if the judge does not use the Supreme Court Circular Letter Number 1 of 2017 as a consideration, it may result in defects in the imposition of narcotics abuse penalties, and the decision.